1998
DOI: 10.1089/hum.1998.9.7-1093
|View full text |Cite
|
Sign up to set email alerts
|

Significant Behavioral Recovery in Parkinson's Disease Model by Direct Intracerebral Gene Transfer Using Continuous Injection of a Plasmid DNA–Liposome Complex

Abstract: As an alternative to virus-mediated gene transfer, we previously demonstrated a simple, safe, and efficient transfer of foreign gene into the central nervous system using continuous injection of a plasmid DNA-cationic liposome complex. To explore whether this approach can be applied to the treatment of certain neurological disorders, we used an experimental model of Parkinson's disease (PD) in the present study. Following continuous injection for 7 days, tyrosine hydroxylase (TH) and aromatic L-amino acid deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Similar protection has been reported when exogenous NGF is infused into the ventricles following traumatic brain injury. 11 Recent studies have suggested that cationic liposomemediated gene transfer of therapeutically relevant genes has potential for treatment of neurological disorders such as Parkinson's disease 53 and epileptic seizures. 54,55 This paper provides new evidence that liposome-mediated gene transfer can produce nine-to 12-fold increases of secreted transgene products in the CSF and that these increases are associated with reductions in neuronal damage following traumatic brain injury.…”
Section: Figure 6 Ngf Gene Transfer Attenuates Cholinergic Neuronal Imentioning
confidence: 99%
“…Similar protection has been reported when exogenous NGF is infused into the ventricles following traumatic brain injury. 11 Recent studies have suggested that cationic liposomemediated gene transfer of therapeutically relevant genes has potential for treatment of neurological disorders such as Parkinson's disease 53 and epileptic seizures. 54,55 This paper provides new evidence that liposome-mediated gene transfer can produce nine-to 12-fold increases of secreted transgene products in the CSF and that these increases are associated with reductions in neuronal damage following traumatic brain injury.…”
Section: Figure 6 Ngf Gene Transfer Attenuates Cholinergic Neuronal Imentioning
confidence: 99%
“…One way to achieve repeated CNS administration is to implant a cannula connected to a subcutaneous reservoir that provides continuous infusion of a therapeutic gene. 10,11 For gene delivery into the spinal cord, a less invasive method, thus potentially allowing multiple administrations, is lumbar intrathecal injection into the cerebrospinal fluid (CSF). Lumbar puncture poses little danger to the spinal cord as the relative wide subarachnoid space at the site allows a certain degree of mobility of nerves within the CSF, thus avoiding damage caused by needle puncture.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures include direct transfer in vivo of the TH cDNA to striatal cells via viral vectors, 54,135,[142][143][144] transplanting cells which have been transduced ex vivo to express TH, 87,[145][146][147][148][149][150] and administration of a DNA-liposome complex encoding TH. [151][152][153] More recently the full pathway of DA synthesis been included in this approach, with the additional transfer of the synthetic enzyme GTPcyclohydrolase (GTPCH) to generate the TH cofactor, tetrahydrobiopterin, 55,[154][155][156] as well as transfer of aromatic amino acid decorboxylase (AADC) to facilitate conversion of L-Dopa to DA. [157][158][159] Together these genes may maximize production of DA in the striatum.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%